Wintering Conditions and Heat Loss during Hibernation in the Brown Long-Eared Bat - Grzegorz Kłys; Joanna Makuchowska-Fryc (Applied Sciences, 2024)
The aim of this study was to estimate heat loss in the brown long-eared bat during hibernation depending on the refugioclimate conditions. The measured values of refugioclimate parameters were: ambient temperature (Ta) 3–10 °C, relative humidity (Rh) 74–98% and air velocity (v) 0.06–0.95 m/s. Heat loss was calculated using convective heat transfer equations. Mean heat loss amounted to 4 W/m2. The results were compared to the heat loss calculated based on the fat burned during hibernation. Bats flying into underground systems during the hibernation period were captured and their body mass was measured. A loss of body mass of 2.6 g over the 126 days of hibernation was observed. Heat loss equalled 3.115 W/m2K.The presented method of calculating energy expenditure allows for non-invasive monitoring of the heat and fat losses of bats during hibernation. Such research may find application in designing artificial wintering sites.